Why does subordinates’ negative workplace gossip lead to supervisor undermining? A moderated mediation model - Zeng, Hao; Zhao, Lijing; Li, Jinsheng (Frontiers in Psychology, 2022)
Objectives: Previous studies on negative workplace gossip have neglected the role of gossip targets of supervisors. The purpose of this paper is to deepen our understanding of how subordinates’ negative workplace gossip affects supervisors’ work-related behaviors. Drawing upon conservation of resource theory, the authors propose that subordinates’ negative gossip leads to supervisor emotional exhaustion. In turn, such emotional exhaustion provokes supervisors to exhibit undermining toward their subordinates. Additionally, the authors propose that a trait factor, namely, supervisor mindfulness, mitigates the relationship between such negative workplace gossip and supervisors’ emotional exhaustion. Method: Data were collected from employees (e.g., subordinates) and their immediate supervisors in 35 organizations located in Jiangsu and Anhui Provinces in China. The data were obtained at three time points, each time interval was 2 weeks, and finally, 362 valid data points were obtained. Results: The following findings were obtained: (1) perceived subordinates' negative gossip has a significant positive effect on supervisor undermining; (2) supervisor emotional exhaustion mediates the relationship between perceived subordinates' negative gossip and supervisor undermining; and (3) supervisor mindfulness moderates the relationship between perceived subordinates' negative gossip and supervisor emotional exhaustion and moderates the mediating effect of supervisor emotional exhaustion on the relationship between perceived subordinates' negative gossip and supervisor undermining. Conclusions: Using multisource data and a moderated mediation model, we found that subordinates' negative workplace gossip predicts supervisor undermining through supervisor emotional exhaustion. We also discovered that supervisor mindfulness can buffer the positive relationship between perceived subordinates' negative workplace gossip and supervisor undermining. These findings have important implications for the literature on negative gossip in the workforce, especially the impact of subordinates' negative workplace gossip on supervisors’ responses.